Location of protein synthesis during morphogenesis of Mucor racemosus. - Orlowski, M (1978)
The intracellular location of active protein synthesis was examined during the emergence of germ tubes from both sporangiospores and yeast-phase cells of Mucor racemosus. It was determined that protein synthesis occurs in all regions of the cell and not preferentially at the growing tip.